Extending Postharvest Storage Life of Non-astringent Persimmon cv. Fuyu by 1-MCP Treatments - Kumar, Naveen; Thakur, K. S. (International Journal of Bio-resource and Stress Management, 2018)
Persimmon is the species Diospyros kaki, a tree belonging to the family Ebenaceae and native to the Far East. Originally cultivated in China and Japan, it is also known as Chinese date plum. A research was carried out to understand the potential of the commercial use of 1-MCP (1 methylcyclopropene) to extend the shelf life of the non-astringent persimmon cultivar cv. Fuyu. Persimmon (Diospyros kaki L.) fruit were harvested at the commercial maturity (yellowish orange colour) and then treated with 1-methylcyclopropene (1-MCP) at three different doses (250 ppb, 500 ppb and 750 ppb) for 24 hrs at 20 °C and kept at ambient air temperature (20 °C) for shelf life evaluation. The result showed that the non 1-MCP treated fruit softened within 15 days after harvest, resulting in unacceptable quality as compare to all 1-MCP treated fruits. The 1-MCP treatments at more than 500 ppb inhibited fruit softening for 30 days after harvest in association with suppression of respiration at room temperature and thus helps in retaining the fruit firmness. Treatment with 250 ppb 1-MCP had a limited inhibitory effect on softening. Change in soluble solid content, acid and peel colour occurred during storage, but all these processes were significantly delayed by 1-MCP treatment. These results indicated that 1-MCP is an effective tool for quality improvement and extension of shelf life in persimmon and fruit might be harvested in yellowish orange stage of ripening, at which the most desirable organoleptic attributes had been developed on tree.